Brain-sparing methods for IMRT of head and neck cancer. - Alex Dunlop; Liam Welsh; Dualta McQuaid; Jamie Dean; Sarah Gulliford; Vibeke Hansen; Shreerang Bhide; Chris Nutting; Kevin Harrington; Kate Newbold (PLoS ONE)
Purpose Radical radiotherapy for head and neck cancer (HNC) may deliver significant doses to brain structures. There is evidence that this may cause a decline in neurocognitive function (NCF). Radiation dose to the medial temporal lobes, and particularly to the hippocampi, seems to be critical in determining NCF outcomes. We evaluated the feasibility of two alternative intensity-modulated radiotherapy (IMRT) techniques to generate hippocampus- and brain-sparing HNC treatment plans to preserve NCF. Methods and materials A planning study was undertaken for ten patients with HNC whose planning target volume (PTV) included the nasopharynx. Patients had been previously treated using standard (chemo)-IMRT techniques. Bilateral hippocampi were delineated according to the RTOG atlas, on T1w MRI co-registered to the RT planning CT. Hippocampus-sparing plans (HSRT), and whole-brain/hippocampus-sparing fixed-field non-coplanar IMRT (BSRT) plans, were generated. DVHs and dose difference maps were used to compare plans. NTCP calculations for NCF impairment, based on hippocampal dosimetry, were performed for all plans. Results Significant reductions in hippocampal doses relative to standard plans were achieved in eight of ten cases for both HSRT and BSRT. EQD2 D40% to bilateral hippocampi was significantly reduced from a mean of 23.5 Gy (range 14.5-35.0) in the standard plans to a mean of 8.6 Gy (4.2-24.7) for HSRT (p = 0.001) and a mean of 9.0 Gy (4.3-17.3) for BSRT (p < 0.001). Both HSRT and BSRT resulted in a significant reduction in doses to the whole brain, brain stem, and cerebellum. Conclusion We demonstrate that IMRT plans for HNC involving the nasopharynx can be successfully optimised to significantly reduce dose to the bilateral hippocampi and whole brain. The magnitude of the achievable dose reductions results in significant reductions in the probability of radiation-induced NCF decline. These results could readily be translated into a future clinical trial.